Saccostrea scyphophilla - Wells, Fred E.; Lukehurst, Sherralee S.; Fullwood, Laura A. F.; Harvey, Euan S. (Zenodo, 2024)
Saccostrea scyphophilla (Peron and Lesueur, 1807) (Figures 2b, 3; Table 1) Brief description of shell: Shell large, up to 10cm in length, very heavy. Usually occurs as individuals that in dense assemblages do not extend over each other. Upper surface rounded. Shell off white, margins purplish. Interior whitish, adductor muscle scar on right valve may be a deep purple. Records in the present survey: Ashburton Port area: Direction Island; East end Thevenard Island; Ashburton Island; Salt Creek; Old Onslow jetty, Beadon Point. Dampier Port area: Withnell Bay; Southern entrance to King Bay; Norbill Bay, Rosemary Island; Whalers Bay, Malus Island; Marney Bay, Malus Island; High Point, Whittaker Island; North side of East Intercourse Island. Port Hedland Port area: Public boat ramp; Finucane Island. Previous records in the Pilbara verified by DNA sequences: Lam and Morton (2006): Vlamingh Head, north of Exmouth; Barrow Island; Withnell Bay, Burrup Peninsula (all as S. mordax (Gould, 1850). Snow et al. (2023): Flying Foam Passage, north of Burrup Peninsula. Published distribution (based on DNA analyses): Okinawa, Taiwan, Hong Kong, China, Singapore, northern Australia (Western Australia, Northern Territory, Queensland, New South Wales) (Lam and Morton 2006 (as S. mordax ); McDougall 2020; McDougall et al. 2020; Snow et al. 2023). Notes: Saccostrea scyphophilla also occurred on a wide variety of habitats, from isolated rocks, intertidal rock platforms, mangroves and artificial structures on both open and protected shores, sometimes at high densities. It frequently co-occurred with Saccostrea lineage A, but was more common on open, exposed shores than Saccostrea lineage A. Snow et al. (2023) commented that S. scyphophilla in WA was previously reported as two lineages, A and B by Lam and Morton (2006), with B being very rare. Snow et al. (2023) considered that the differences between lineages were relatively small and combined the two, a practice followed here. Published as part of Wells, Fred E., Lukehurst, Sherralee ...